Intrinsic hippocampal functional connectivity underlying rigid memory in children and adolescents with autism spectrum disorder: A case–control study. (October 2021) - Hashimoto, Teruo; Yokota, Susumu; Matsuzaki, Yutaka; Kawashima, Ryuta
Atypical learning and memory in early life can promote atypical behaviors in later life. Less relational learning and inflexible retrieval in childhood may enhance restricted and repeated behaviors in patients with autism spectrum disorder. The purpose of this study was to elucidate the mechanisms of atypical memory in children with autism spectrum disorder. We conducted picture–name pair learning and delayed-recognition tests with two groups: one group with high-functioning autism spectrum disorder children (aged 7–16, n  = 41) and one group with typically developing children ( n  = 82) that matched the first group's age, sex, and IQ. We assessed correlations between successful recognition scores and seed-to-whole-brain resting-state functional connectivity. Although both learning and retrieval performances were comparable between the two groups, we observed slightly lower category learning and significantly fewer memory gains in the autism spectrum disorder group than in the typically developing group. The right canonical anterior hippocampal network was involved in successful memory in youths with typically developing, while other memory systems may be involved in successful memory in youths with autism spectrum disorder. Context-independent and less relational memory processing may be associated with fewer memory gains in autism spectrum disorder. These atypical memory characteristics in autism spectrum disorder may accentuate their inflexible behaviors in some situations. Lay abstract: Atypical learning and memory in early life can promote atypical behaviors in later life. Specifically, less relational learning and inflexible retrieval in childhood may enhance restricted and repeated behaviors in patients with autism spectrum disorder. The purpose of this study was to elucidate the mechanisms of atypical memory in children with autism spectrum disorder. We conducted picture–name pair learning and delayed-recognition tests with two groups of youths: one group with high-functioning autism spectrum disorder children (aged 7–16, n  = 41) and one group with typically developing children ( n  = 82) that matched the first group's age, sex, and full-scale IQ. We examined correlations between successful recognition scores and neural connectivity during resting in the magnetic resonance imaging scanner without thinking about anything. Although both learning and retrieval performances were comparable between the two groups, we observed significantly fewer memory gains in the autism spectrum disorder group than in the typically developing group. The memory network was involved in successful memory retrieval in youths with typically developing, while the other memory systems that do not depend to a great degree on networks may be involved in successful memory in youths with autism spectrum disorder. Context-independent and less relational memory processing may be associated with fewer memory gains in autism spectrum disorder. In other words, autism spectrum disorder youths might benefit from non-relational memory. These atypical memory characteristics in autism spectrum disorder may exaggerate their inflexible behaviors in some situations, or—vice versa—their atypical behaviors may result in rigid and less connected memories.